2011
DOI: 10.4244/eijv7i7a132
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous renal artery intervention versus medical therapy in patients with renal artery stenosis: a meta-analysis

Abstract: We did not find a significant improvement in blood pressure or renal function in patients with renal artery stenosis treated with renal artery revascularisation compared to medical therapy alone. However, trial quality was a limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In a systematic review, 54 the authors concluded that EPDs may be beneficial in some patients, but there was inadequate empirical data to clearly define the risk/benefit. In a small four-arm randomized study of 100 patients, it was noted that the use of adjuvant IIb/IIIa glycoprotein inhibitors and EPDs may have a synergistic benefit.…”
Section: Endovascular Therapy For Aras and Progression Of The Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, 54 the authors concluded that EPDs may be beneficial in some patients, but there was inadequate empirical data to clearly define the risk/benefit. In a small four-arm randomized study of 100 patients, it was noted that the use of adjuvant IIb/IIIa glycoprotein inhibitors and EPDs may have a synergistic benefit.…”
Section: Endovascular Therapy For Aras and Progression Of The Diseasementioning
confidence: 99%
“…57 Another meta-analysis study showed no benefit between the two arms. 54 Some studies have shown that the only benefit is blood pressure control, not renal function. 55,58,59 …”
Section: Endovascular Therapy For Aras and Progression Of The Diseasementioning
confidence: 99%
“…Moreover, a meta-analysis did not find an improvement in blood pressure (BP) in patients with renal artery stenosis treated with renal artery stenting. 4 Therefore, a double mechanism maintains hypertension: renovascular and sympathetic tone. In the following, we report the case of a patient with RH treated by RDN after renal artery stenting.…”
mentioning
confidence: 99%
“…16,17 This lack of benefit could be related to the fact that most patients with RAS may have essential hypertension complicated by a renovascular disease. It is also possible that a late chronic stage of RAS hypertension is no longer directly dependent on the RAA system but on local vasoconstrictor and proliferative effects in the arterial wall leading to renal artery revascularization inefficacy.…”
mentioning
confidence: 99%